Differential equations / Paul Blanchard; Robert L Devaney; Glen R Hall - Blanchard, Paul
This text on differential equations seeks to strike a balance between analytic, numeric and graphical techniques, emphasizes modelling, stresses qualitative theory throughout the course, uses technology, and presents linear and nonlinear systems in parallel.